Synaptic Mitochondria in Synaptic Transmission and Organization of Vesicle Pools in Health and Disease - Vos, Melissa; Lauwers, Elsa; Verstreken, Patrik (Frontiers in Synaptic Neuroscience, 2010)
Cell types rich in mitochondria, including neurons, display a high energy demand and a need for calcium buffering. The importance of mitochondria for proper neuronal function is stressed by the occurrence of neurological defects in patients suffering from a great variety of diseases caused by mutations in mitochondrial genes. Genetic and pharmacological evidence also reveal a role of these organelles in various aspects of neuronal physiology and in the pathogenesis of neurodegenerative disorders. Yet the mechanisms by which mitochondria can affect neurotransmission largely remain to be elucidated. In this review we focus on experimental data that suggest a critical function of synaptic mitochondria in the function and organization of synaptic vesicle pools, and in neurotransmitter release during intense neuronal activity. We discuss how calcium handling, ATP production and other mitochondrial mechanisms may influence synaptic vesicle pool organization and synaptic function. Given the link between synaptic mitochondrial function and neuronal communication, efforts towards better understanding mitochondrial biology may lead to novel therapeutic approaches of neurological disorders including Alzheimer’s disease, Parkinson’s disease, amyotrophic lateral sclerosis and psychiatric disorders that are at least in part caused by mitochondrial deficits.